Routledge handbook on men, masculinities and organizations : theories, practices and futures of organizing / edited by Jeff Hearn, Kadri Aavik, David L. Collinson and Anika Thym. - Hearn, Jeff, 1947-; Aavik, Kadri, 1980-; Collinson, David L., 1957-; Thym, Anika (Routledge international handbooks., 2024)
Provides new theoretical and empirical insights into men men's practices and masculinities across many kinds of organizations and forms of organizing.